Moléculas y formulaciones con nombres extraños o antiguos - Plée, Dominique (2013)
Through history, the names of many molecules have changed. It is interesting to remember those forgotten names and to try to track their origin. There are also molecules that are not so well known and which have peculiar names which are able to induce smiles or astonishment to English speaking people (especially those who understand the slang). Nevertheless, it’s not necessary to be a Shakespeare’s fan to understand and appreciate this funny nomenclature.